Study of the Flypaper Effect Phenomenon on Regency/City Financial Performance in Bengkulu Province - Feronica Zadha Valentina; Retno A. Eka Putri (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
This research aims to examine whether the Flypaper Effect phenomenon exists in the Regency/city in Bengkulu Province by finding the influence of Regional Original Income (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) on Regional Expenditures. This study uses panel data obtained from the publication of financial statistics from the Central Bureau of Statistics of Bengkulu Province for 2015-2022. The data and hypothesis testing used is multiple regression analysis on EViews9. The test results from this research show that the Flypaper Effect phenomenon occurred in Regency/cities in Bengkulu Province in 2015-2022. This can be seen from the value of the Regional Original Income Coefficient (PAD) which is not significant towards Regional Expenditures.